SERUM LEVEL OF SOLUBLE INTERLEUKIN-2 RECEPTOR ALPHA AS A PREDICTOR OF TREATMENT RESPONSE IN BRUCELLOSIS - Kahbazi, Manije; Rezapour, Hamidreza; Jafari, Farshad; Arjomandzadegan, Mohammad; Sofian, Masume; Zarinfar, Nader; Sarmadiayan, Hossein; Najmi, Amir Reza (Journal of Ayub Medical College Abbottabad, 2012)
Introduction: Iran is one of the endemic regions with high prevalence of brucellosis. Several serological markers for diagnosis and response to treatment are available. Serum level of Soluble Interleukin-2 Receptor alpha (SIL-2Rα) is a new marker to assess response to therapy and clinical relapse of brucellosis. This study intends to investigate the serum levels of SIL-2Rα before and after treatment, to evaluate this marker for patients responding to treatment of brucellosis. Methods: This study is an analytical cross-sectional study. Forty patients who had clinical signs of brucellosis and serological tests confirmed the disease have been treated with standard antibiotics for 6 weeks. 2ME and SIL-2Rα levels were measured before and after treatment and these values were compared. Results: Among the 40 patients, 27 patients (67.5%) had improvement in symptoms and 13 patients (32.5%) had no symptoms after treatment. In Comparing serum levels of SIL-2Rα and 2ME before and after treatment, decreasing of both markers after treatment was significant (p<0.001). In patients with false positive for 2ME, SIL-2Rα in 57% of patients had a reduction, but in patients with false negative for 2ME, SIL-2Rα in only 28% of patients increased. Conclusion: Not only is Serum level of SIL-2Rα useful for predicting response to treatment of brucellosis, but also in cases of false positive of 2ME can be helpful. Keywords: Brucellosis, SIL-2Rα, 2ME